Exploring barriers to residential heat pump adoption: a UK case study of user behaviour - Gao, Lin; Naylor, Philip; Hegab, Abdelrahman; Pilidis, Pericles (MDPI, 2026)
With heat pump adoption falling behind expectations, the UK faces a strategic challenge in meeting residential decarbonisation targets. This study investigates the barriers hindering adoption through an in-depth case analysis of a complete household heat pump adoption journey in a pre-Second World War family home in the UK. Combining an autoethnographic approach with quantitative analysis of 4.7 years of household data, it provides a rare, detailed examination of consumer experience in the UK. The analysis applies both rational and relational perspectives, showing that relational factors, such as trust and social networks, are particularly influential in early-stage markets. Key challenges are identified in retrofit system complexity, social engagement, installer capability and electricity pricing. Although the initial assessment found the heat pump was uneconomic, post-installation results showed an annual SPF of 3.22, a 59% reduction in energy demand and a 12% reduction in costs compared with a gas boiler. Behavioural adaptation contributed to demand reduction and lowered the effective electricity price by ~3 pence/kWh. However, a further 7 pence/kWh reduction is required to reach cost parity with a gas boiler, implying an electricity-to-gas price ratio of 2.3. The findings highlight important areas for policy intervention.
This article belongs to the Section C: Energy Economics and Policy
Keywords: Generic health relevance; 7 Affordable and Clean Energy; 33 Built environment and design; 40 Engineering; 51 Physical sciences; heat pump; gas boiler; residential heating; buildings; adopter decision-making; seasonal performance factor; energy efficiency; decarbonisation; energy policy